2005
DOI: 10.1111/j.1745-6584.2005.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vertical Hydraulic Conductivity of an Aquitard at Two Spatial Scales

Abstract: Aquitards protect underlying aquifers from contaminants and limit recharge to those aquifers. Understanding the mechanisms and quantity of ground water flow across aquitards to underlying aquifers is essential for ground water planning and assessment. We present results of laboratory testing for shale hydraulic conductivities, a methodology for determining the vertical hydraulic conductivity (K(v)) of aquitards at regional scales and demonstrate the importance of discrete flow pathways across aquitards. A regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 21 publications
(31 reference statements)
5
51
1
Order By: Relevance
“…The (homogeneous) properties of all sealing layers are representative of shale formations suitable for trapping CO 2 , with small permeability and high capillary entry pressure for supercritical CO 2 . With the focus on the multilayer impact of CO 2 injection, which depends strongly on the properties of the sealing layers, we have varied seal permeability over a wide range: k s = 1.0 Â 10 À16 to 1.0 Â 10 À21 m 2 -based on shale permeabilities reported in Neuzil (1994), Domenico and Schwartz (1998), Hovorka et al (2001), and Hart et al (2006) plus one case with an impermeable seal for comparison. Notice that the van Genuchten model was used to calculate the capillary pressure and relative permeability of the two-phase flow in all simulation cases (Van Genuchten, 1980).…”
Section: Model Parametersmentioning
confidence: 99%
“…The (homogeneous) properties of all sealing layers are representative of shale formations suitable for trapping CO 2 , with small permeability and high capillary entry pressure for supercritical CO 2 . With the focus on the multilayer impact of CO 2 injection, which depends strongly on the properties of the sealing layers, we have varied seal permeability over a wide range: k s = 1.0 Â 10 À16 to 1.0 Â 10 À21 m 2 -based on shale permeabilities reported in Neuzil (1994), Domenico and Schwartz (1998), Hovorka et al (2001), and Hart et al (2006) plus one case with an impermeable seal for comparison. Notice that the van Genuchten model was used to calculate the capillary pressure and relative permeability of the two-phase flow in all simulation cases (Van Genuchten, 1980).…”
Section: Model Parametersmentioning
confidence: 99%
“…to 10 -16 m 2 (Neuzil, 1994;Domenico and Schwartz, 1998;Hovorka et al, 2001;Hart et al, 2006). Hart et al (2006) recently measured the permeability of shale aquitards of the Maquoketa Formation in Wisconsin, and found the permeability to range from 2.5 10 -21…”
Section: Seal Propertiesmentioning
confidence: 99%
“…In this case, the saline aquifer acts like a "semi-closed" system ( Figure 3, bottom), allowing some fraction of the displaced brine to migrate into and through the overlying and underlying sealing units, which in turn would increase the storage capacity for CO 2 . The importance of this vertical inter-layer communication will mostly depend on the permeability of the seals, which can vary widely depending on their hydrogeological characteristics (e.g., Neuzil, 1994;Domenico and Schwartz, 1998;Hovorka et al, 2001;Hart et al, 2006 The quick-assessment method is based on the fact that the injected CO 2 needs to displace native brine of an equivalent volume, and that this equivalent volume is comprised of three volume contributions that can be easily calculated: (1) the additional pore volume within the storage formation provided by pore and brine compressibility in response to pressure buildup; (2) the additional pore volume within the sealing units provided by pore and brine compressibility in response to pressure buildup; and (3) With these goals in mind, this section is structured as follows: Section 3.2 introduces the hypothetical formation-seal systems analyzed and discusses the different sensitivity cases with varying geometric and hydrogeologic properties; Section 3.3 describes the quickassessment method for estimating the pressure buildup and storage capacity in closed and semi-closed systems; Section 3.4 gives simulated results showing the observed pressure buildup and CO 2 plume evolution for a range of conditions; and Section 3.5 demonstrates the applicability and validity of the quick-assessment method through comparison against the simulated results.…”
Section: Introductionmentioning
confidence: 99%
“…Hanson et al (2004) modeled groundwater flow in the Santa Clara Valley of California and estimated that approximately 19% of flow from shallower to deeper strata occurred through wells. Hart et al (2006) investigated potential flow mechanisms responsible for a discrepancy between core-scale and regional estimates of vertical conductivity for an aquitard in Wisconsin, USA. Using a combination of numerical and analytical modeling, they found that flow through a single well could be approximately 700 l/min and a spacing of one well every 10 km would be sufficient to account for the difference in flow implied by the different estimates of hydraulic conductivity.…”
Section: Previous Researchmentioning
confidence: 99%